Sargassum fusiforme polysaccharide attenuates high‐sugar–induced lipid accumulation in HepG2 cells and Drosophila melanogaster larvae. Issue 10 (12th August 2021) - He, Dan; Yan, Liping; Zhang, Jiaqi; Li, Fang; Wu, Yu; Su, Laijin; Chen, Peichao; Wu, Mingjiang; Choi, Jong‐il; Tong, Haibin
Abstract: Lipid accumulation is a major factor in the development of non‐alcoholic fatty liver disease (NAFLD). Currently, there is a lack of intervention or therapeutic drugs against NAFLD. In this study, we investigated the ability of Sargassum fusiforme polysaccharide (SFPS) to reduce lipid accumulation induced by high sugar in HepG2 cells and Drosophila melanogaster larvae. The results indicated that SFPS significantly ( p  < .01) decreased the accumulation of lipid droplets in high sugar–induced HepG2 cells. Furthermore, SFPS also suppressed the expression of Srebp and Fas (genes involved in lipogenesis) and increased the expression of PPARɑ and Cpt1 (genes that participated in fatty acid β‐oxidation) in these cells. SFPS markedly reduced the content of triglyceride of the third instar larvae developed from D. melanogaster eggs reared on the high‐sucrose diet. The expression of the Srebp and Fas genes in the larvae was also inhibited whereas the expression of two genes involved in the β‐oxidation of fatty acids, Acox57D‐d and Fabp, was increased in the larval fat body (a functional homolog of the human liver). We also found that SFPS ameliorated developmental abnormalities induced by the high‐sucrose diet. These results of this study suggest that SFPS could potentially be used as a therapeutic agent for the prevention and treatment of NAFLD. Abstract : In the present study, we first demonstrated that polysaccharide (SFPS) from medicinal and edible brown alga Sargassum fusiform showed lipid‐lowering activity by inhibiting lipogenesis and promoting fatty acid β‐oxidation in vitro and in vivo. We also found that high sugar–induced developmental retardation was ameliorated by SFPS activity. Meanwhile, SFPS is a natural phytochemical that reduces hepatic lipid accumulation, suggesting that it has potential applications in the prevention or treatment of nonalcoholic fatty liver disease and health promotion.